La desaparición de la República Democrática Alemana. Contexto internacional y crisis interna, 1989-1990 - Pacheco Méndez, Guadalupe (El Colegio de México A.C., 2015)
The reforms promoted by Mikhail Gorbachev in the Soviet Union destabilized the communist regime of the GDR, opening up a process that combined internal factors with international negotiations on the democratization of the GDR and the unification of the two Germanies. A method of inserting unified Germany into the international system was required that would boost European stability following the shift in the balance of power arising from the crisis in the Soviet empire, and the presence of a strong Germany at the heart of the continent. Access for the GDR to the institutional framework of the German Federal Republic resolved the international problem, but curtailed the democratization process begun in the GDR.